Jonathan D. Hill & Jean-Pierre Chaumeil (Orgs) | Burst of Breath: New Research on Indigenous Ritual Wind Instruments in Lowland South America - Izomar Lacerda; Kaio Domingues Hoffmann (Revista de Antropologia, 2014)
HILL, Jonathan D. & CHAUMEIL, Jean-Pierre (Orgs). Burst of Breath: New Research on Indigenous Ritual Wind Instruments in Lowland South America. Lincoln: University of Nebraska, 2011, 440 pp.